PREFERENSI PETANI TERHADAP SISTEM TANAM PADI (Kasus Desa Nembol Kecamatan Mandalawangi Pandeglang Banten) - aliudin, Aliudin; Maysiyah, Maysiyah; saleh, Khaerul (Jurnal Penyuluhan dan Pemberdayaan Masyarakat, 2022)
The purpose of this research is to identify and to analyze farmers' preference for the rice planting system in Nembol Village, Mandalawangi Pandeglang District. This research use quantitative descriptive research, as it’s type and located at Nembol Village, Mandalawangi District, Pandeglang. The research are using random sampling technique. This research use 50 rice farmers, as it’s respondents. Chi-square test analysis are being used for the data processing and descriptive analysis are being used for the analysis methods. The results shows that the factors that related to the farmers' preference for the rice planting system are, age, level of education, length of farming, status of land ownership. While the characteristics, the length of time to apply the planting system, number of family dependents, land area, and land productivity are not related to the farmers' cropping system preference. Farmers' preference for the rice planting system this shows that the preference of farmers towards the mini-cropping system is still relatively low because most farmers in the Nembol Village, Mandalawangi Pandeglang District prefer non-minapadi cropping systems.